Third Hankel Determinant for Certain Class of Bazilevi'{c} Functions Associated with Linear Differential Operator - Al-khafaji, Saba N.; Hussain, Ahmed Hadi; Abbas, Sameer Annon (Discontinuity, Nonlinearity, and Complexity, 2026)
The main object of this paper is to introduce a new class of Bazilević functions $Ω^n_α(m, δ)$ in the open unit disk $\mathbb{D}$ associated with linear differential operator. In addition to, we obtained the coefficient estimates as well as best possible upper bound to the third Hankel determinant for the functions belong to this class.